Pengabaian Suku Asli dalam Proses Perdamaian di Kolombia - Farhan Helmi Siregar (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2018)
Peace talks between the Goverment of Republic of Colombia with Fuerzas Armadas Revolucionarias de Colombia—Ejército del Pueblo (FARC-EP) started from 2011 to 2016, and followed by disarmament and transition phase until 2017. The talks and process have resulted peace agreement between the conflicting sides in 2016, FARC-EP disarmament process, and transitioning the rebels into civilians’ life. Considered as a success by some observers, the peace process is not yet solving the problem about indigenous people affected by an half-century conflict between the goverment and FARC-EP. This paper will examine discourses from perspective of community security which is originated from the concept of human security that involves violent action, and other threats towards indigenous people in Colombia, the Awa, and Wounaan People between 2011 to 2017. The goal of discursive practices on violent action towards indigenous ''people during the peace process in Colombia is to explain the threat to community security in Colombia due to the problem occured in indigenous community